Pendampingan Guru Tahfizh dalam Mengontrol Kelancaran Hafalan Al-Qur’an Anak di Rumah Tahfizh Darul Musthafa Padang - Nur Lubis, Khairan; Kustati, Martin; Gusmirawati (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Based on the phenomenon that children often have difficulty memorizing the Qur'an outside of class hours, the role of tahfizh teachers is very important in maintaining the quality of children's memorization, in terms of fluency, consistency, and encouragement to repeat. The purpose of this mentoring program is to help children at Rumah Tahfizh Darul Musthafa memorize the Qur'an fluently, monitor their progress, build motivation, overcome difficulties in memorization, and improve the quality of their Qur'an memorization. This service method uses Participatory Action Research (PAR), which addresses children's difficulties in memorizing the Qur'an through collaboration between teachers and parents in advancing Qur'an memorization. Children, parents, and tahfizh teachers are actively involved in every phase of the activity. The results of the mentoring program show that tahfizh teachers are able to significantly improve the quality of children's memorization with the help of joint monitoring and evaluation strategies, as well as active communication with parents. Teachers and parents work together to create plans that suit each child's needs. Therefore, the guidance of tahfizh teachers not only helps academically but also builds discipline, incentives, and a supportive atmosphere for children to memorize the Qur'an. Keywords: Guidance for tahfizh teachers, memorization of the Qur'an, Rumah Tahfizh.